Characteristics of telogen effluvium in COVID-19 in western Iran (2020), - Khaled Babaei; Hossein Kavoussi; Mansour Rezaei; Reza Kavoussi (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Although COVID-19 pandemic significantly induces mortality, many of the patients who recovered present other medical problems such as alopecias. Telogen effluvium is a common alopecia that is usually related to previous events such as acute febrile diseases, including COVID-19. Objective: To evaluate the characteristics of telogen effluvium in COVID-19. Method: This cross-sectional study was carried out on 526 patients with documented telogen effluvium that recovered from COVID-19. Demographic data, concurrent alopecia, associated diseases, and COVID-19 severity were recorded. Data were analyzed by appropriate statistical methods. Results: The mean age of the 526 patients (410 females, 116 males) was 30.97±9.592 years, with 7.65 ± 1.739 weeks of mean time of alopecia onset. Vitamin D deficiency (24.3%), androgenetic alopecia (78.2%), and grade III COVID-19 severity were the most common findings. Alopecia onset was significantly earlier in the younger age group, females, in hypothyroidism, and more severe coronavirus infection. Higher grade coronavirus infection was significantly seen in males, higher ages, earlier onset, and androgenic alopecia. Study limitations: Performing a single-center study and considering limited variables. Conclusion: Although Coronavirus 2 infection can be an important factor in telogen effluvium induction, other factors such as associated diseases, drug intake and emotional stress may also be involved. In the cases of early onset of alopecia, concomitant diseases such as hypothyroidism and severe coronavirus infection can occur, thus, the presence of various factors in telogen effluvium induction should be considered.